The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.plefa.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat intake and red blood cell fatty acid composition of children and women from three different geographical areas in South Africa

Abstract: Dietary fat intake, particularly the type of fat, is reflected in the red blood cell (RBC) fatty acid (FA) profile and is vital in growth, development and health maintenance. The FA profile (%wt/wt) of RBC membrane phospholipids (as determined by gas chromatography) and dietary intake (as determined by 24h recall) was assessed in 2-6y old South African children and their caregivers randomly selected from three communities, i.e. an urban Northern Cape community (urban-NC; n=104), an urban coastal Western Cape c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Generally, the quantitative accuracy of DR or 24-h recall is thought to be superior to that of the food frequency questionnaire (FFQ). Most of the other studies using DR or 24-h recall with smaller numbers of participants also reported that ARA intakes were around 100 mg/day or more, although there are some exceptions (Table 4) [28,[42][43][44][45][46][47][48]. These studies suggest that ARA intake, at least in advanced countries, is 100-250 mg/day for normal healthy adults.…”
Section: Dietary Intake Of Aramentioning
confidence: 96%
See 1 more Smart Citation
“…Generally, the quantitative accuracy of DR or 24-h recall is thought to be superior to that of the food frequency questionnaire (FFQ). Most of the other studies using DR or 24-h recall with smaller numbers of participants also reported that ARA intakes were around 100 mg/day or more, although there are some exceptions (Table 4) [28,[42][43][44][45][46][47][48]. These studies suggest that ARA intake, at least in advanced countries, is 100-250 mg/day for normal healthy adults.…”
Section: Dietary Intake Of Aramentioning
confidence: 96%
“…Although a similar situation may be infrequent in advanced countries, it may occur in developing countries. ARA intake was reported to be 33-34 [41] or 39 mg/day [47] in rural areas of South Africa, which is approximately one-third of that in respective urban areas. In any case, it is expected that additional high-quality nutritional data of dietary ARA intake in various countries and groups will accumulate.…”
Section: Dietary Intake Of Aramentioning
confidence: 99%
“…Some groups reported increased cholesterol-to-phospholipid ratios (McBride and Jacob, 1970;Biemer, 1980;Barenholz et al, 1981) while others detected increased total cholesterol content without any increase in the cholesterol-to-phospholipid ratio (Iida et al, 1984) and still others described no alterations at all of the total cholesterol amount (Simon and Ways, 1964). Fatty acid composition was also largely maintained in pHypoβ RBCs, except for the slight increase of the linoleic and arachidonic acids, which could be related to specific dietary intake (Takkunen et al, 2013;Ford et al, 2016). To the best of our knowledge, the fatty acid content has not been studied in heterozygous hypobetalipoproteinemia.…”
Section: Alteration Of Membrane Lipid Lateral Distribution Representsmentioning
confidence: 98%
“…[5] Furthermore, ALA is an essential nutrient and should be consumed as part of a mixed diet. Dietary guidelines for LCn3 include eating two portions of fish per week (one being oily fish) to provide 500 mg/day of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), [6] and to increase the intake of flax seeds, chai seeds, hemp seeds, walnuts, soybean and/or canola to ensure sufficient ALA intake. South Africans generally do not meet the basic dietary guidelines for ALA, EPA and DHA.…”
Section: Implications For Practicementioning
confidence: 99%
“…South Africans generally do not meet the basic dietary guidelines for ALA, EPA and DHA. [6] While this review focused on the effects of LCn3 and ALA, a healthy dietary pattern that consists of fruit and vegetables, nuts, whole grains and dietary fibre, together with sodium restriction and reduced intake of sugar and sugar-sweetened beverages, [5] is important for the primary and secondary prevention and treatment of CVD. Furthermore, the relationship between the intake of omega-3 and omega-6 polyunsaturated fatty acids (PUFA) influences health outcomes.…”
Section: Implications For Practicementioning
confidence: 99%